Analisis Pengaruh Inflasi, Produk Domestik Bruto (PDB), Nilai Tukar Mata Uang Asing dan Suku Bunga Terhadap Profitabilitas Bank Umum Syariah di Indonesia (Studi Kasus Bank Muamalat Periode 2007-2023) - Zuhdi , Muhammad Naufal; Wulandari, Ries; Setyowati, Eni (Neolectura, 2024)
This research aims to analyze the influence of Inflation, Gross Domestic Product, Exchange Rates and Interest Rates on the profitability of Islamic banking, especially Bank Muamalat. This research uses descriptive quantitative methods. The data in this research is secondary time series data published by the Central Statistics Agency (BPS), Bank Indonesia (BI), Financial Services Authority (OJK). The data analysis technique uses multiple linear regression analysis which has previously been tested with classical assumptions. The results of multiple linear regression include that inflation and exchange rates have a significant effect on RoA, GDP and interest rates do not have a significant effect on RoA and inflation, economic growth, exchange rates and interest rates have a significant effect on Return on Assets of Bank Muamalat for the 2007-2023 period.